Identification of agronomic characters of F1 rice plants derived from crossing Inpara 8 and Inpago 12 varieties - Syafira Zulfa Hidayanti; Rujito Agus Suwignyo (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Suboptimal rice productivity in the swamp was due to both drought stress and submergence stress during the lifetime of the rice, and swamp rice could only be planted once a year. One of the efforts to increase the productivity of swamp rice was to develop rice varieties that can tolerate drought stress and submergence stress. The study aimed to validate the success of the F1 cross and to develop rice varieties exhibiting dual tolerance through backcrossing. Data analysis utilized Analysis of Variance followed by 5% test. The planting method uses a Randomized Complete Block Design (RCBD) with three replications. Observed variables included plant height, number of tillers per clump, number of panicles per clump, number of grains per panicle, number of grains per clump, weight of grain per panicle, dry weight of harvested grain, dry weight of grain, weight of 1000 grains, percentage of empty grains, flowering age, and harvesting age. Evaluations of growth characteristics revealed no significant differences in genetic traits and characteristics between the crossed rice and the parental lines. Flowering age and harvesting age of rice Inpago 12 elders were faster than Inpara 8 elders. Plant height of Inpago 12 elders was higher than Inpara 8 elders. This was due to differences in genetic traits and characters between varieties, and finally it was concluded that F1 accessions were successfully crossed and did not single-cross.